2009
DOI: 10.1074/jbc.m809757200
|View full text |Cite
|
Sign up to set email alerts
|

WISP1, a Pro-mitogenic, Pro-survival Factor, Mediates Tumor Necrosis Factor-α (TNF-α)-stimulated Cardiac Fibroblast Proliferation but Inhibits TNF-α-induced Cardiomyocyte Death

Abstract: WNT1-inducible signaling pathway protein-1 (WISP1), a member of the CYR61/CTGF/Nov family of growth factors, can mediate cell growth, transformation, and survival. Previously we demonstrated that WISP1 is up-regulated in post-infarct heart, stimulates cardiac fibroblast proliferation, and is induced by the proinflammatory cytokine tumor necrosis factor-␣ (TNF-␣).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 64 publications
(66 reference statements)
5
104
1
Order By: Relevance
“…43296; Active Motif, Carlsbad, CA) (30,39). Activation of NF-B was also confirmed by reporter assays using adenoviral transduction of an NF-B reporter vector (Ad.NF-B-Luc, MOI 50) (38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43296; Active Motif, Carlsbad, CA) (30,39). Activation of NF-B was also confirmed by reporter assays using adenoviral transduction of an NF-B reporter vector (Ad.NF-B-Luc, MOI 50) (38).…”
Section: Methodsmentioning
confidence: 99%
“…Binding of Sp1 to the EMMPRIN 5=-cis regulatory region in vivo was determined by chromatin immunoprecipitation (ChIP) assay. ACMs were treated with IL-18 (5 ng/ml for 2 h), and the ChIP assay carried out as previously described (7,39). Immunocomplexes were prepared using anti-Sp1 antibody (sc-14027 X, Santa Cruz Biotechnology,).…”
Section: Methodsmentioning
confidence: 99%
“…Given that Wisp1 was upregulated following Bmp3 treatment and is a known pro-survival factor in various nonadipose cell types (Inkson et al 2009, Königshoff et al 2009, Venkatachalam et al 2009, Schlegelmilch et al 2014, coupled with previous findings that human adipocyte differentiation was associated with elevated Wisp1 expression (Murahovschi et al 2015), we examined the involvement of Wisp1 in mediating Bmp3-induced MSC proliferation. We first determined if Bmp3-induced upregulation of Wisp1 expression preceded Bmp3-stimulated cell proliferation by conducting a time-dependent experiment.…”
Section: Effects Of Bmp3 On Wisp1 Expression and Msc Proliferationmentioning
confidence: 99%
“…Among the significantly upregulated genes, WNT-inducible secreted protein 1 (Wisp1/CCN4), whose expression was upregulated 3.7-fold by Bmp3 (Fig. 1A), was of particular interest, because it has been previously shown to promote proliferation of cardiac fibroblasts (Venkatachalam et al 2009), lung epithelial cells (Königshoff et al 2009) and osteogenic cells (Inkson et al 2009). Consequently, we selected Wisp1 as a potential candidate gene and verified the magnitude of the increase in levels of Wisp1 mRNA following Bmp3 treatment with qRT-PCR ( Fig.…”
Section: Effects Of Bmp3 On Msc Transcriptomementioning
confidence: 99%
“…These domains determine the function of CCN member proteins during development and in human diseases. Although Wisp1 has been linked to oncogenic transformation (Pennica et al 1998;Xu et al 2000), proliferation and cell survival (Venkatachalam et al 2009;Venkatesan et al 2010), and epithelial-to-mesenchymal transition (Konigshoff et al 2009), little is known about its downstream genes or how it regulates their expression. In this study, we identified several downstream ECM components that were regulated by Wisp1, likely through its interaction with biglycan.…”
Section: Discussionmentioning
confidence: 99%